Assessment of Medical Students’ Knowledge and Practices in the Rehabilitation of Diabetic Patients Through Lifestyle Modifications - Dr. Saleh Khalid Al Mogairen (South Eastern European Journal of Public Health, 2025)
Background: Lifestyle modifications play a pivotal role in the rehabilitation of diabetic patients by improving glycemic control and preventing complications. Medical students, as future healthcare providers, must possess the necessary knowledge and skills to effectively counsel patients on these interventions. This study aimed to assess the knowledge and practices of medical students regarding lifestyle modifications for diabetes rehabilitation and identify barriers to implementation. Methods: A cross-sectional study was conducted among 328 medical students at King Faisal University, Al-Ahsa, Saudi Arabia. Data were collected using a structured, self-administered questionnaire covering demographics, knowledge, practices, and perceived barriers. Knowledge and practice scores were analyzed using descriptive and inferential statistics. Results: The mean knowledge score was 14.8 ± 3.2 out of 20, with 43.3% demonstrating moderate knowledge and 36.3% high knowledge. Clinical students scored significantly higher than preclinical students (15.7 ± 3.1 vs. 13.5 ± 3.4, p < 0.001). Only 37.5% of students reported regular counseling practices, despite 60.4% feeling confident in discussing lifestyle changes. Common barriers included lack of time (71.4%), insufficient training (63.1%), and low patient adherence (56.4%). Conclusion: While medical students exhibited moderate-to-high knowledge of lifestyle modifications, gaps in practice and significant barriers highlight the need for enhanced curricular integration of lifestyle medicine. Structured training programs and practical experiences are essential to equip students for effective diabetes rehabilitation.